ISLAM AND SECULARISM - Al-Attas, Syed Muhammad Naquib (Ta`dib International Sdn Bhd, 2022)
this book is one of the most creative and original works of a Muslim thinker in the contemporary Muslim world. The author deals with fundamental problems faced by contemporary Muslims and provides real solutions, beginning with a discussion on ‘The Contemporary Western Christian Background’ in Chapter (I), followed by his analysis of the concepts (which he newly defines) of ‘secular’, ‘secularization’, and ‘secularism’ in Chapter (II). All this is then contrasted in Chapter (IV) of the book entitled ‘Islam: The Concept of Religion and the Foundation of Ethics and Morality’